Taking body temperature, inside out [body temperature monitoring]. - Jones, W.D (IEEE spectrum)
Originally developed in the mid-1980s by NASA for monitoring the body temperatures of astronauts on the Space Shuttle, the "radio pill" has now found a new application in the football field. Several pro and college teams have begun issuing these multivitamin-size pills to players who they think might be at risk for heatstroke. Once swallowed, the pill acts as an internal thermometer, providing continuous readings of a player's body temperature, which can be picked up by a sensor placed against the small of the player's back. The radio pill relies on a temperature-sensitive quartz crystal oscillator whose vibration frequencies are well known for temperatures ranging from -60°C to 150°C.